Use of medium chain triglyceride (MCT) oil in subjects with Alzheimer's disease: A randomized, double‐blind, placebo‐controlled, crossover study, with an open‐label extension - Angela G. Juby; Toni E. Blackburn; Diana R. Mager (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction Cerebral glucose and insulin metabolism is impaired in Alzheimer's disease (AD). Ketones provide alternative energy. Will medium chain triglyceride (MCT) oil, a nutritional source of ketones, impact cognition in AD? Methods This was a 6‐month randomized, double‐blind, placebo‐controlled, crossover study, with 6‐month open‐label extension in probable AD subjects, on stable medications. MCT dose was 42 g/day, or maximum tolerated. Cognition was assessed with Mini‐Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), and Cognigram®. Results Twenty subjects, average age 72.6 years, 45% women, 70% university educated had baseline MMSE 22.6/30 (10–29); MoCA 15.6/30 (4–27); baseline Cognigram® Part 1: 65–106, Part 2: 48–107. Average MCT oil consumption was 1.8 tablespoons/day (25.2 g, 234 kcal). Eighty percent remained stable or improved. Longer MCT exposure and age > 73, resulted in higher final MMSE (P < .001) and Cognigram® 1 scores. Discussion This is the longest duration MCT AD study to date. Eighty percent had stabilization or improvement in cognition, and better response with 9‐month continual MCT oil.